Korelasi Brand Ambassador NCT 127 dengan Sikap Konsumen Blibli - Indar Amila Azizah; Witanti Prihatiningsih (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to see how much the credibility of NCT 127 as a brand ambassador has a relationship with the consumer attitude of Blibli using source credibility theory. This theory explains that a person is considered credible if he has characteristics, like expertise, trustworthiness, and attractiveness. The method used in this research is quantitative with a correlational approach. The sample in this study was taken using a probability sampling technique with a simple random sampling method. In collecting data, researchers used survey methods in the form of questionnaires distributed to one hundred respondents. The criteria for respondents in this research must be individuals who follow the Instagram account @bliblidotcom and using the Blibli application during the NCT 127 period as Blibli brand ambassadors. The data obtained is then processed using a correlation test and hypothesis testing (t-test). The final results of this study show that the higher credibility of NCT 127 as a brand ambassador, the higher altitude of Blibli consumers. In addition, based on the results of the correlation test, it can be concluded that of the three components of credibility, the trustworthiness aspect has a strong degree of relationship with consumer attitudes, while the expertise aspect has a moderate or sufficient degree of relationship, and the attractiveness aspect has a low degree of relationship.